Processo penal e política criminal : uma reconfiguração da justa causa para a ação penal - Divan, Gabriel Antinolfi (2014)
The present thesis has as a goal to discuss the new configurative-conceptual basis to the institution of the fair/minimum cause for the prosecution. It pursuits to present a vision based on the criminal-political analysis of the Estate s activity in managing conflicts criminally relevant and to evaluate in a critical way the interventionism that it results. Spheres of action on conflict managing, interest and social relations that goes from examples tuned to a social self-management of events to a verticalism that aims the manipulation and guidance of the consequences of it will be demonstrated, going through several levels and instances of political guidance. It pursuits to establish, in this context, an amplified notion of criminal policy that covers not only a single ideological content related to punitive laws and its conceptual motivation, but also a wider spectrum that deals with this specific issue not as a synonym of criminal policy , but as part of a great set of thoughts that are shown as representative layers of many levels of Estate s interventionism in managing social conflictive interests and relations. In this sense, the criminal legal system, described as a set of rules, knowledge, uses and activities that permeates the criminal persecution, criminal procedure, criminal laws and imprisonment, is a vertical level or moment of intervention and not the only interventional device or use verified and relevant. From this proposed political-criminal view, results contributions of a procedural policy where also the levels of the intervention verticalism can be visualized and exemplified in characteristics that go from the ex officio action of the Judge in conducting procedural works to an own (self)critic verification of the function or procedural instrumentality related to the prosecution. The paper aims to show elements of this procedural policy promoting a theoretical review of concepts of action and the principology concerning the criminal procedure: its condition and the prinicipology around its prosecution. Hereupon, it establishes the principle of obligatoriness as a simple political choice of action, not having any structural connection between the option for the referred principle and solid elements related to the (procedural) claim manifested by the prosecution in the criminal procedure, neither to any right defended in the prosecution or filling mentioned. The claim related to the prosecution of a criminal action has a differentiated feature which has no univocal relation with an eventual claim of material law and therefore cannot be used as a refuge to reflect the misconception that militates for the idea that the adoption of criteria of (political) convenience to the exercise of the action violates fundamental precepts. The two final chapters of the thesis expatiate about the fair cause for the prosecution in a distinct way, however complementary. First, it is presented the surnamed traditional view of the institute in its criminal and procedural tints, and studied the conceptual evolution of the institute along with the exposition of the critic related to that view and the contributions that deserve to be reconfigured. In a second moment, it is exposed the renovation of the institute from a critical view of the jurisdictional action as an intervention of the Estate in the social sphere, proposing a view of the fair cause for the prosecution as a polymorphic institute which lends to the global analysis of the necessity/utility of the intervention, that could be used as a political-criminal scope for a decision that claims for the no political interference of the Estate, in many ways: procedural/penal, criminological and social-philosophical.